Deletion of a Genetic Region of lp17 Affects Plasmid Copy Number in Borrelia burgdorferi - Wong, Jessica K.; Crowley, Michael A.; Bankhead, Troy (Frontiers in Cellular and Infection Microbiology, 2022)
Borrelia burgdorferi, the Lyme disease pathogen, is maintained in its enzootic life cycle through complex gene regulatory pathways encoded on its uniquely fragmented genome. This genome consists of over 20 plasmids, and the regulatory mechanisms of plasmid maintenance and replication are largely unknown. The bbd21 gene, encoded on lp17 and a member of the paralogous family 32 proteins, was originally proposed to be a putative parA orthologue involved with plasmid partitioning; however, this function has not been confirmed to date. To determine the role of bbd21 in B. burgdorferi, we utilized targeted gene deletion and discovered bbd21 and bbd22 are co-transcribed. The effects of bbd21 and bbd22 deletion on plasmid copy number and mammalian infectivity were assessed. By qPCR, lp17 copy number did not differ amongst strains during mid-exponential and stationary growth phases. However, after in vitro passaging, the mutant strain demonstrated an 8-fold increase in lp17 copies, suggesting a cumulative defect in plasmid copy number regulation. Additionally, we compared lp17 copy number between in vitro and mammalian host-adapted conditions. Our findings showed 1) lp17 copy number was significantly different between these growth conditions for both the wild type and bbd21-bbd22 deletion mutant and 2) under mammalian host-adapted cultivation, the absence of bbd21-bbd22 resulted in significantly decreased copies of lp17. Murine infection studies using culture and qPCR demonstrated bbd21-bbd22 deletion resulted in a tissue colonization defect, particularly in the heart. Lastly, we showed bbd21 transcription appears to be independent of direct rpoS regulation based on similar expression levels in wild type and ΔrpoS. Altogether, our findings indicate the bbd21-bbd22 genetic region is involved with regulation of lp17 plasmid copy number. Furthermore, we propose the possibility that lp17 plasmid copy number is important for microbial pathogenesis by the Lyme disease spirochete.